Fiscal Policy Multipliers in Small States - Alichi, Ali (IMF Working Papers; Working Paper, 2019)
Government debt in many small states has risen beyond sustainable levels and some governments are considering fiscal consolidation. This paper estimates fiscal policy multipliers for small states using two distinct models: an empirical forecast error model with data from 23 small states across the world; and a Dynamic Stochastic General Equilibrium (DSGE) model calibrated to a hypothetical small state's economy. The results suggest that fiscal policy using government current primary spending is ineffective, but using government investment is very potent in small states in affecting the level of their GDP over the medium term. These results are robust to different model specifications and characteristics of small states. Inability to affect GDP using current primary spending could be frustrating for policymakers when an expansionary policy is needed, but encouraging at the current juncture when many governments are considering fiscal consolidation. For the short term, however, multipliers for government current primary spending are larger and affected by imports as share of GDP, level of government debt, and position of the economy in the business cycle, among other factors.